Prefrontal haemodynamics based classification of inter-individual working memory difference - De, A (Electronics letters, 2020)
This Letter illustrates prefrontal haemodynamics as a neurovascular basis of inter-personal working memory differences. A functional near-infrared spectroscopy with sampling frequency ∼2 Hz is used to record the blood oxyhaemoglobin and deoxyhaemoglobin signals from 19 subjects engaged in working memory task of encoding and retrieval of ten symbol-meaning association learning. The individual difference in working memory performance is classified by supervised learning-based linear discriminant analysis and ensemble classifiers. Prior to the classification approach, individual performance is labelled as high, moderate and low on the basis of the performance index. The spontaneous haemodynamic activity and task-evoked responses are marked as background and foreground signals, respectively, which are scaled by means of stream-independent and stream-dependent models. The classifiers' performance shows that the stream-dependent model-based feature construction-classification improves classification accuracy to a major extent compared to the stream-independent model and no gain model. To understand the neurovascular basis of the inter-individual performance difference, diffused voxel plots are constructed. The voxel plots showed that concurrent activation of orbitofrontal and dorsolateral prefrontal cortex could have a possible association with persons' higher working memory performance.